Experimental study on the load transfer behavior of a deep foundation member induced by the settlement in sand - Park, Suhyuk; Chang, Ilhan (Smart Geotechnics for Smart Societies, 2023)
An experimental test was conducted to assess the bearing capacity and load transfer mechanism of a pile model considering progressive settlement in this study. Dry natural sand (Jumunjin sand) was used to compose a model ground, where the cylindrical soil tank has a dimension of 380 mm in diameter and 900 mm in height. 28 load transducers were embedded at the lower bottom of soil tank to measure the load variation due to pile penetration. A pile model was fabricated with acryl which has a diameter of 80 mm and length of 800 mm. The pile model was fabricated to measure both tip bearing and skin friction without interfering with other measurements. Test variables are the distance between the tip of the pile model and the bottom of the soil container. The experimental setup was available to analyze the bearing capacity and load transfer mechanism at different penetration depths which represents the settlement behavior of pile model.